UJI POTENSI Streptomyces spp ISOLAT MALANG UNTUK MENEKAN PERTUMBUHAN Fusarium sp PADA TANAMAN CABAI RAWIT (Capsicum frutescens L) SECARA IN VITRO - Hakim, Lukman; Mujoko, Tri; Widajati, Wiludjeng (JURNAL AGROTROPIKA, 2025)
Streptomyces spp is a group of actinomycetes bacteria that can be used as biological control agents producing antibiotics Streptomyces spp. proven by its ability to inhibit the pathogen Fusarium sp causing fusarium wilt disease in plants. This study aims to determine the potential of Streptomyces spp isolated from chili rhizosphere soil in Malang city, East Java in controlling Fusarium sp. This research was conducted in vitro at the Plant Health Laboratory 1, Faculty of Agriculture, National Development University "Veteran" East Java in November 2023 using a complete randomized design (CRD) with 10 treatments, namely Streptomyces spp isolates with 3 replications. The results of the study obtained 10 isolates of Streptomyces spp and conducted antagonistic tests with Fusarium sp. Streptomyces isolates 6 and 9 have a higher antagonistic ability compared to other Streptomyces isolates with a percentage of 48.3% and 41.9%.